Enhanced ultraviolet photoresponse in a graphene-gated ultra-thin Si-based photodiode. (9th April 2019) - Li, Guoli; André, Nicolas; Huet, Benjamin; Delhaye, Thibault; Reckinger, Nicolas; Francis, Laurent A; Liao, Lei; Raskin, Jean-Pierre; Zeng, Yun; Flandre, Denis
Abstract: We present an ultra-thin lateral SOI PIN photodiode with transferred monolayer graphene as the transparent gate, to provide enhanced ultraviolet (UV) performance and mechanical flexibility beyond standard Si-based devices. The device dark current shows intact characteristics after the post-CMOS thinning and graphene transfer processing steps. The device responsivity presents high potential in UV and visible wavelength detections (i.e. within the 200–900 nm range) under monochromatic light illumination. A maximum responsivity of 0.18 A W −1 has been experimentally achieved at 390 nm wavelength and validated by simulation, for a diode with intrinsic length L i of 20 μ m. Additionally, the 5 μ m-thick device chip with direct board assembly paves the way towards the development of hybrid flexible electronics.